Responsiveness of SF-36 Health Survey and Patient Generated Index in people with chronic knee pain commenced on oral analgesia: analysis of data from a randomised controlled clinical trial - Papou, Alex; Hussain, Salma; McWilliams, Daniel F.; Zhang, Weiya; Doherty, Michael (Springer International Publishing, 2016)
Purpose. (1) to assess the responsiveness of the Short Form 36 Health Survey (SF-36) and Patient Generated Index (PGI) in people with knee pain who were given oral analgesics; and (2) to perform content analysis of the SF-36 and PGI aiming to identify differences between the instruments and causes of different responsiveness. Methods. An observational study nested within a randomised controlled trial comparing oral paracetamol, ibuprofen or a combination of the two in 884 community-derived people with chronic knee pain. Each participant was given the SF-36 and PGI questionnaires to fill out at baseline, day 10, week 7 and week 13 after commencement on analgesia. Responsiveness was measured as a standardised response mean from baseline and contents of the instruments were analysed. Results. The PGI showed the greater responsiveness to analgesics than the SF-36 throughout the study period. Only the Bodily Pain Score of the SF-36 showed comparable responsiveness to the PGI. The standardised response mean of the PGI at 13 weeks was 0.61 (95% confidence interval 0.51 to 0.72), and that of the Bodily Pain Score of the SF-36 was 0.49 (95% confidence interval 0.39 to 0.58). Content analysis of the PGI identified multiple areas which are not represented in the SF-36 which may help explain its performance. Conclusions. Overall the PGI is more responsive than the SF-36 to commonly used oral analgesics taken for knee pain. The PGI is able to elicit areas of individualised health related quality of life which are not captured by the SF-36.